Preparation method of nano silicon dioxide composite organic silicon coating
By emulsion polymerization in the Si-N bond-containing organosiloxane/persulfate redox system, copolyfluorosilicone modified silica nanoparticles and combined with the silicone resin to form a nanosilica composite silicone coating, the problem that the surface energy and mechanical properties of the silicone coating in the prior art cannot be improved simultaneously, and efficient anti-fouling and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411673890.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The existing silicone coatings are difficult to improve mechanical properties while improving surface energy, and cannot meet the application needs of antifouling coatings in marine environments.
By emulsion polymerization in a Si-N bond-containing organosiloxane/persulfate redox system, copolyfluorosilicone modified silica nanoparticles and bonded with the silicone resin to form a nanosilica composite silicone coating.
The low surface energy and high mechanical properties of the silicone coating are achieved while improving, with the water contact angle reaching above 115°, the diiodomethylantiol contact angle reaching above 95°, the surface energy is reduced to below 11mJ m-2, and the tensile strength reaches above 0.6MPa.
Smart Images

Figure CN119505696A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organosilicon coatings, and in particular to a method for preparing a nano-silicon dioxide composite organosilicon coating. Background Art
[0002] Low surface energy antifouling coatings are also called non-toxic antifouling coatings, which mainly refer to low surface energy antifouling coatings based on fluorocarbon resins and organosilicon compounds. Their common characteristics are that they do not contain toxic substances and have very low surface energy. From the perspective of environmental protection, non-toxic antifouling coatings are undoubtedly the most attractive choice for antifouling coatings. The reason why they are called antifouling coatings is that due to their unique surface properties, the adhesion interface of the fouling on them is very weak, and they can be easily removed by using their own weight, the impact of water flow during navigation, or the cleaning of auxiliary equipment.
[0003] Current research focuses on low surface energy antifouling coatings based on silicone and organic fluorine. Among them, the research on silicone antifouling coatings focuses on small molecule silicone oil modification and modified coating matrix. The performance of pure silicone materials is slightly insufficient when used in antifouling coatings. The mechanical properties of silicone materials are poor and it is difficult to be used in marine environments. In actual applications, the integrity of the paint film is easily destroyed, and the damaged areas are easily colonized and attached by fouling organisms and are difficult to repair. The research on organic fluorine antifouling coatings focuses on fluorinated acrylates and perfluoropolyethers, but fluorinated polymers are expensive and costly.
[0004] The application of nano-silica to reinforce resin-based polymer materials has a long history, and the existing technology obtains nanoparticles with lower surface energy by grafting fluorine-containing functional groups on the surface to construct micro-nano multi-scale amphiphilic coatings. However, nano-silica has hydrophilic groups that are easy to agglomerate. The method of introducing nanoparticles to construct a micro-nano structure on the coating surface to obtain a low surface energy surface affects the coating performance due to the uneven dispersion of nanoparticles in the matrix. The reinforcement effect of nano-silica on silicone materials is difficult to meet the needs of anti-fouling coating applications.
[0005] In March 2022, Guan Jiawei prepared three types of functionalized silica in the article "Preparation and Performance Study of Functionalized Silica Modified Silicone Coatings" and applied them to modified reinforced silicone coatings. Among them, atom transfer radical polymerization was used to introduce natural antifouling active molecules eugenol and fluorinated hydrophobic monomer octafluoropentyl methacrylate on the silica surface to prepare grafted natural antifouling active molecules nano-silica and made into silicone coatings. After the polymerization of fluorinated monomers was initiated on the surface of nano-silica, fluorinated polymer chains would precipitate on the surface of the coating. When the addition amount of functionalized silica was 5%, the water contact angle of the coating was 120.05°, and the coating's inhibition rates on boat algae and triangular brown finger algae were 94.09% and 90.73%, respectively.
[0006] However, the above antifouling coating cannot simultaneously achieve the low surface energy and high mechanical properties of the silicone coating. Summary of the invention
[0007] The invention provides a method for preparing a nano-silicon dioxide composite organosilicon coating, which solves the problem that the surface energy and mechanical properties of the existing organosilicon coating cannot be improved simultaneously.
[0008] In order to solve the above technical problems, the technical solution of the method for preparing the nano-silicon dioxide composite organosilicon coating of the present invention is:
[0009] A method for preparing a nano-silicon dioxide composite organic silicon coating comprises the following steps:
[0010] 1) subjecting silica nanoparticles, acryloxyalkylalkoxysilane and fluorinated acrylate to emulsion polymerization in an organosiloxane / persulfate redox system containing Si-N bonds under the action of an emulsifier to obtain a fluorine-silicon modified silica nanoparticle emulsion;
[0011] 2) The fluorine-silicon modified silica nanoparticle emulsion obtained in step 1), silicone resin, coupling agent, crosslinking agent and catalyst are mixed to obtain silicone coating, which is then coated on a substrate and crosslinked and cured to obtain a nano-silicon dioxide composite silicone coating.
[0012] The present invention is an improvement on the prior art, and provides a preparation method of a nano-silicon dioxide composite organosilicon coating. The method comprises the following steps: performing emulsion polymerization in an organosiloxane / persulfate redox system containing Si-N bonds, copolymerizing unsaturated alkoxysilane and fluorine-containing acrylate, and utilizing hydrolysis crosslinking of multiple Si-O of the organosiloxane containing Si-N bonds to connect the copolymerized acrylic acid-containing chain segments into a network, and crosslinking with the hydroxyl groups on the surface of the silicon dioxide, thereby initiating polymerization on the surface of the silicon dioxide; and grafting the alkoxy groups in the copolymer onto the fluorine-containing acrylate. The surface of nano-silica realizes the fluorine-silicon modification of silica nanoparticles, improves the dispersibility of silica in the silicone coating, and the functionalized nano-silica is introduced into the silicone coating. The chemical bonds formed by the hydrolysis and condensation of the siloxane of the silicone matrix and the hydroxyl groups on the silica surface combine the silica with the silicone matrix. The functionalized functional groups introduced can improve the hydrophobicity and oleophobicity of the coating (the amphiphobicity of the coating), and the water contact angle reaches more than 115°, and the diiodomethane contact angle reaches more than 95°. It also has a low surface energy, as low as 11mJ m -2 The following improves the mechanical properties of the coating, and the tensile strength of the coating reaches above 0.6MPa, while reducing the surface energy of the silicone coating and improving the mechanical properties of the coating.
[0013] The present invention performs emulsion polymerization in an organosiloxane / persulfate redox system containing Si-N bonds, and uses an organosilicon compound containing silicon-nitrogen bonds and ammonium persulfate as redox initiators, so that the polymerization reaction can be carried out in an aqueous phase without the need to react in an organic solvent. The reaction can be carried out at room temperature and is easy to control. The product of the emulsion polymerization is not easy to agglomerate and the reaction time is short.
[0014] In order to further improve the properties of the copolymer grafted on the surface of the silica nanoparticles and improve the surface energy and mechanical properties of the coating, preferably, the acryloxyalkylalkoxysilane is γ-methacryloxypropyltrimethoxysilane, and the fluorine-containing acrylate is dodecafluoroheptyl methacrylate.
[0015] In order to further increase the density of grafted functional groups of silica nanoparticles, preferably, the molar ratio of the acryloxyalkylalkoxysilane to the fluorinated acrylate is (2.5-3):(4.5-5), and the mass ratio of the silica nanoparticles to the acryloxyalkylalkoxysilane is (0.9-1):(7-8).
[0016] In order to further improve the mechanical properties of the organic silicon coating while reducing the surface energy of the coating, preferably, the mass ratio of the organic silicon resin to the silicon dioxide nanoparticles is (90-100): (0.9-1).
[0017] In order to further reduce the start-up energy of emulsion polymerization, preferably, the organosiloxane containing Si-N bonds has a structure shown in Formula I:
[0018]
[0019] In Formula I, R1, R2, R3, R 10 , R 11 and R 12 Each is independently selected from C1-C5 alkyl; R4 and R5 are independently selected from C1-C6 alkylene; R6, R7, R8 and R9 are independently selected from methyl, ethyl or propyl;
[0020] The persulfate is selected from one or more of ammonium persulfate, potassium persulfate and sodium persulfate.
[0021] In order to further reduce the start-up energy of emulsion polymerization, preferably, the mass ratio of the Si-N bond-containing organosiloxane to the persulfate is (1.5-2):(0.1-0.5), and the added amount of the Si-N bond-containing organosiloxane is 20-25% of the mass of the acryloxyalkylalkoxysilane.
[0022] In order to further improve the initiation rate during the emulsion polymerization, preferably, an alkali metal salt is introduced as a promoter during the emulsion polymerization in step 1), wherein the alkali metal salt is selected from one or more of calcium chloride, sodium chloride and lithium chloride, and the amount of the alkali metal salt added is 0.8-1% of the mass of the acryloxyalkylalkoxysilane. The alkali metal salt can stabilize the free radicals generated in the water phase during the emulsion polymerization and improve the initiation rate.
[0023] In order to further reinforce the organosilicon coating, preferably, fumed silica with a particle size of 8 to 16 nm is added during mixing in step 2), and the mass ratio of the organosilicon resin to the fumed silica is (90 to 100): (4 to 4.5).
[0024] In order to further improve the curing efficiency of the silicone coating, preferably, in step 2), the mass ratio of the silicone resin, coupling agent, crosslinking agent and catalyst is (90-100): (1.8-3): (9-10): (0.2-0.4).
[0025] In order to further improve the curing efficiency of the silicone coating, preferably, the coupling agent in step 2) is 3-aminopropyltriethoxysilane and aminosilane polymer; the cross-linking agent is vinyltrimethoxysilane; the catalyst is dibutyltin dilaurate; and the mass ratio of 3-aminopropyltriethoxysilane to aminosilane polymer is (0.9-1.5):(0.9-1.5). BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a flow chart of the nano-silicon dioxide composite organosilicon coating of Example 1 of the present invention;
[0027] Figure 2 This is a schematic diagram of the reaction principle of SiO2-SiF in Example 1 of the present invention;
[0028] Figure 3 This is a picture of the SiO2-SiF emulsion of Example 1 of the present invention;
[0029] Figure 4 This is a photo of a coating formed by applying the organosilicon coating of Example 1 of the present invention on a cement board;
[0030] Figure 5 TEM image and EDS image of SiO2-SiF of Example 1 of the present invention;
[0031] Figure 6 This is the XPS spectrum of SiO2-SiF in Example 1 of the present invention;
[0032] Figure 7 is an AFM 3D image of the organosilicon coating of Example 1 of the present invention;
[0033] Figure 8 This is a photo of the contact angle test of the silicone coating;
[0034] Fig. 9 This is a stress-strain curve diagram of the silicone coating of Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The technical concept of the preparation method of the nano-silicon dioxide composite organic silicon coating of the present invention is as follows:
[0036] The existing technology is to first graft silane coupling agent KH550 and bromoisobutyryl bromide (BIBB) on the surface of silica, then introduce eugenol methacrylate (EMA) monomer to undergo polymerization reaction, and finally introduce octafluoropentyl methacrylate (FMA) monomer to undergo polymerization to form functionalized nanoparticles SiO2-KH550-BIBB-EMA-FMA. The antifouling effect of the natural active product eugenol and the hydrophobicity of the fluorinated monomer octafluoropentyl methacrylate are utilized. During the curing process of the silicone material, the fluorinated chain segments migrate to the coating surface to stabilize it. At the same time, the chain segments with antifouling activity are also precipitated on the surface, which is beneficial to inhibit small biological fouling and further improve the antifouling performance of the material.
[0037] The present invention grafts a copolymer of acryloxyalkylalkoxysilane and fluorine-containing acrylate on the surface of silica through emulsion polymerization, utilizes the hydrolysis cross-linking of multiple Si-O of organic siloxane containing Si-N bonds, connects the acrylic acid-containing chain segments into a network, and cross-links with the hydroxyl groups on the surface of silica, thereby initiating polymerization on the surface of silica, improving the dispersibility of silica nanoparticles in the organic silicon coating, and after the organic silicon coating is introduced, the functionalized nano-silica combines silica with the organic silicon matrix through the chemical bonds formed by silane condensation, and utilizes the functionalized silica to improve the hydrophobicity and oleophobicity of the coating, reduce the surface energy of the coating, slow down the adhesion of contaminants on the coating, and improve the mechanical properties of the coating, so that it is not easy to be damaged in practical applications, thereby increasing the life of the coating.
[0038] The preparation method of the nano-silicon dioxide composite organosilicon coating of the present invention is specifically as follows: 1) mixing an aqueous dispersion of silicon dioxide nanoparticles, an emulsifier aqueous solution, an acryloxyalkyl alkoxy silane and a fluorine-containing acrylate, and then respectively adding an organosiloxane containing a Si-N bond, a persulfate and an alkali metal salt aqueous solution dropwise under stirring conditions, and obtaining a fluorine-silicon-modified silicon dioxide nanoparticle emulsion after an emulsion polymerization reaction, wherein the water in the emulsion participates in the polymerization of organosilicon in the coating; and 2) mixing the fluorine-silicon-modified silicon dioxide nanoparticle emulsion obtained in step 1), an organosilicon resin, fumed silica, a coupling agent, a crosslinking agent and a catalyst to obtain an organosilicon coating, and coating the mixture on a substrate and crosslinking and curing the mixture to obtain a nano-silicon dioxide composite organosilicon coating.
[0039] In a specific embodiment, the emulsifier is OP-20, and the mass ratio of acryloxyalkylalkoxysilane to the emulsifier is (7-8):(0.9-1).
[0040] In a specific embodiment, the concentration of the silica nanoparticle aqueous dispersion is 2.5-3%; the concentration of the emulsifier aqueous solution is 9-10%.
[0041] In a specific embodiment, the emulsion polymerization reaction time is 1 to 2 hours.
[0042] In a specific embodiment, in step 2), fumed silica with particle sizes of 8 nm and 16 nm is added during mixing, and the mass ratio of fumed silica with particle sizes of 8 nm and 16 nm is (2-2.25):(2-2.25).
[0043] The organosiloxane containing Si-N bonds is prepared according to the method described in patent CN115490805A.
[0044] In a specific embodiment, the organosiloxane containing Si-N bonds is TBPDD, and the chemical formula of TBPDD is as follows:
[0045]
[0046] In a specific implementation manner, the organic silicon resin used is methyl-terminated 107 silicone rubber with a viscosity of 1000 to 15000 Pa·s.
[0047] The embodiments of the present invention are further described below in conjunction with specific examples. The chemical reagents involved in the following examples are all commercially available conventional products unless otherwise specified.
[0048] 1. Specific embodiments of the method for preparing the nano-silicon dioxide composite organosilicon coating of the present invention
[0049] Example 1
[0050] The flow chart of the nano-silicon dioxide composite organic silicon coating of this embodiment is as follows Figure 1 As shown, the specific preparation method is as follows:
[0051] 1) 0.9 g SiO2 and 0.94 g emulsifier OP-20 are dissolved in 35 g and 10 g water to form SiO2 aqueous dispersion and OP-20 aqueous solution respectively. The SiO2 aqueous dispersion, OP-20 aqueous solution, 7.45 g γ-methacryloxypropyltrimethoxysilane (γ-MPS) and 18 g dodecafluoroheptyl methacrylate (DMFA) are mixed, emulsified by an emulsifier and added to a three-necked bottle. 2 g aqueous solution containing 0.1 g ammonium persulfate (APS) and 0.06 g calcium chloride and 1.5 g TBPDD are added dropwise at a certain stirring speed, and the reaction is carried out for 1 hour. The reaction principle is as follows: Figure 2 As shown, a fluorine-silicon modified silica nanoparticle emulsion is obtained, which is recorded as SiO2-SiF emulsion. Figure 3 As shown;
[0052] 2) After 2.25 g 8 nm, 2.25 g 16 nm fumed silica, 2.7 g SiO2-SiF emulsion obtained in step 1) and 90 g methyl-terminated 107 silicone rubber (viscosity 1500 Pa·s) were mixed uniformly, 0.9 g 3-aminopropyltriethoxysilane and 0.9 g aminosilane polymer (Zhejiang Boiling Point Chemical Co., Ltd., R-8104), 9.9 g vinyltrimethoxysilane and 0.25 g dibutyltin dilaurate were added, and it was ensured that the stirred product was mixed uniformly after each addition, and finally an organosilicon coating was prepared, which was applied to a cement board and cross-linked and cured in the air at room temperature to obtain a nano-silica composite organosilicon coating. The coating photo is shown in FIG. Figure 4 shown.
[0053] 2. Experimental Examples
[0054] Experimental Example 1
[0055] This experimental example characterizes the SiO2-SiF obtained in Example 1. Figure 5 TEM and EDS images of SiO2-SiF. Figure 5 It can be seen that after emulsion polymerization, C, F, O, Si, and N elements are distributed on the surface of silica particles, proving the successful grafting of γ-methacryloxypropyltrimethoxysilane and dodecafluoroheptyl methacrylate. This indicates that the hydroxyl groups on the surface of silica hydrolyze and condense with the siloxy groups of the organosiloxane, and TBPDD and ammonium persulfate act as redox initiators to initiate the polymerization reaction of the unsaturated bonds of γ-methacryloxypropyltrimethoxysilane and dodecafluoroheptyl methacrylate.
[0056] Figure 6 is the XPS spectrum of SiO2-SiF, from Figure 6It can be seen that the surface of the modified particles contains elements such as N, F, and Si, indicating the successful grafting of γ-methacryloxypropyltrimethoxysilane and dodecafluoroheptyl methacrylate.
[0057] Experimental Example 2
[0058] This experimental example characterizes and tests the performance of the nano-silicon dioxide composite organosilicon coating obtained in Example 1.
[0059] The effect of nano-silica functionalization on the surface morphology of the coating was evaluated by AFM testing. Figure 7 AFM 3D image of nano-silicon dioxide composite organic silicon coating. Figure 7 It can be seen that protrusions appear on the surface of the silicone coating, which should be modified silica particles.
[0060] The hydrophobicity and oleophobicity of the coating were evaluated by contact angle test, and the surface energy of the coating was tested. The test results of water contact angle, diiodomethane contact angle and surface energy are shown in Table 1, and the contact angle test photos are shown in Figure 8 As shown, Figure 8 a and b are the water contact angle photos and diiodomethane contact angle photos of the organic silicon coating without the introduction of modified particles SiO2-SiF, respectively. Figure 8 c and d are the water contact angle photos and diiodomethane contact angle photos of the silicone coating of Example 1, respectively. Figure 8 It can be seen that compared with the organosilicon coating without the introduction of modified particles, the water contact angle and diiodomethane contact angle of the organosilicon coating of the present invention are increased, and the surface energy of the coating is reduced, indicating that the introduction of SiO2-SiF into the coating can improve the amphiphobicity of the organosilicon coating and reduce the surface energy of the coating, thereby slowing down the adhesion of contaminants on the coating, making the contaminants easier to remove.
[0061] Table 1 Contact angle and surface energy test results of coatings
[0062]
[0063] The mechanical properties of the coating were characterized by tensile tests. A national standard sample of silicone material with a thickness of 2±0.2 mm was prepared according to GB / T1024.2-2006. The tensile speed was set to 50 mm / mm. The measured stress-strain curve was as follows: Fig. 9 As shown, from Fig. 9 It can be seen that compared with the organosilicon coating without the introduction of SiO2-SiF, the fracture strength of the organosilicon coating of the present invention is greatly improved from 0.37 MPa to 0.60 MPa, and the elongation at break is increased from 186% to 271%.
[0064] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nano-silicon dioxide composite organosilicon coating, characterized in that: The following steps are involved: 1) subjecting silica nanoparticles, acryloxyalkylalkoxysilane and fluorinated acrylate to emulsion polymerization in an organosiloxane / persulfate redox system containing Si-N bonds under the action of an emulsifier to obtain a fluorine-silicon modified silica nanoparticle emulsion; 2) The fluorine-silicon modified silica nanoparticle emulsion obtained in step 1), silicone resin, coupling agent, crosslinking agent and catalyst are mixed to obtain silicone coating, which is then coated on a substrate and crosslinked and cured to obtain a nano-silicon dioxide composite silicone coating.
2. The method for preparing a nano-silicon dioxide composite organic silicon coating according to claim 1, characterized in that: The acryloxyalkylalkoxysilane is γ-methacryloxypropyltrimethoxysilane, and the fluorine-containing acrylate is dodecafluoroheptyl methacrylate.
3. The method for preparing a nano-silicon dioxide composite organic silicon coating according to claim 1 or 2, characterized in that: The molar ratio of the acryloxyalkylalkoxysilane to the fluorine-containing acrylate is (2.5-3):(4.5-5), and the mass ratio of the silicon dioxide nanoparticles to the acryloxyalkylalkoxysilane is (0.9-1):(7-8).
4. The method for preparing the nano-silicon dioxide composite organosilicon coating according to claim 1, characterized in that: The mass ratio of the silicone resin to the silicon dioxide nanoparticles is (90-100): (0.9-1).
5. The method for preparing the nano-silicon dioxide composite organosilicon coating according to claim 1, characterized in that: The Si-N bond-containing organosiloxane has a structure shown in Formula I: In Formula I, R1, R2, R3, R 10 , R 11 and R 12 Each is independently selected from C1-C5 alkyl; R4 and R5 are each independently selected from C1-C6 alkylene; R6, R7, R8 and R9 are each independently selected from methyl, ethyl or propyl; The persulfate is selected from one or more of ammonium persulfate, potassium persulfate and sodium persulfate.
6. The method for preparing the nano-silicon dioxide composite organosilicon coating according to claim 1 or 5, characterized in that: The mass ratio of the organic siloxane containing Si-N bonds to the persulfate is (1.5-2):(0.1-0.5), and the added amount of the organic siloxane containing Si-N bonds is 20-25% of the mass of the acryloxyalkylalkoxysilane.
7. The method for preparing the nano-silicon dioxide composite organosilicon coating according to claim 1, characterized in that: In step 1), an alkali metal salt is introduced as a promoter during emulsion polymerization. The alkali metal salt is selected from one or more of calcium chloride, sodium chloride and lithium chloride. The amount of the alkali metal salt added is 0.8-1% of the mass of the acryloxyalkylalkoxysilane.
8. The method for preparing the nano-silicon dioxide composite organosilicon coating according to claim 1, characterized in that: In step 2), fumed silica with a particle size of 8 to 16 nm is added during mixing, and the mass ratio of the silicone resin to the fumed silica is (90 to 100): (4 to 4.5).
9. The method for preparing a nano-silicon dioxide composite organic silicon coating according to claim 1, characterized in that: In step 2), the mass ratio of the silicone resin, coupling agent, crosslinking agent and catalyst is (90-100): (1.8-3): (9-10): (0.2-0.4).
10. The method for preparing the nano-silicon dioxide composite organic silicon coating according to claim 1 or 9, characterized in that: The coupling agent in step 2) is 3-aminopropyltriethoxysilane and aminosilane polymer; the crosslinking agent is vinyltrimethoxysilane; the catalyst is dibutyltin dilaurate; the mass ratio of 3-aminopropyltriethoxysilane to aminosilane polymer is (0.9-1.5):(0.9-1.5).
Citation Information
Patent Citations
Nano-silica modified silicon resin super-hydrophobic coating, and preparation method and application thereof
CN111154396A
Hydrogel initiated based on redox reaction
CN115490805A
Organic silicon coating super-hydrophobic coating and preparation method thereof
CN116804132A